Sex differences in hippocampal β-amyloid accumulation in the triple-transgenic mouse model of Alzheimer’s disease and the potential role of local estrogens - Hu, Yu-Ting; Chen, Xin-Lu; Zhang, Ya-Nan; McGurran, Hugo; Stormmesand, Jochem; Breeuwsma, Nicole; Sluiter, Arja; Zhao, Juan; Swaab, Dick; Bao, Ai-Min (Frontiers in Neuroscience, 2023)
Introduction Epidemiological studies show that women have a higher prevalence of Alzheimer’s disease (AD) than men. Peripheral estrogen reduction during aging in women is proposed to play a key role in this sex-associated prevalence, however, the underlying mechanism remains elusive. We previously found that transcription factor early growth response-1 (EGR1) significantly regulates cholinergic function. EGR1 stimulates acetylcholinesterase (AChE) gene expression and is involved in AD pathogenesis. We aimed to investigate whether the triple-transgenic AD (3xTg-AD) mice harboring PS1M146V, APPSwe, and TauP301L show sex differences in β-amyloid (Aβ) and hyperphosphorylated tau (p-Tau), the two primary AD hallmarks, and how local 17β-estradiol (E2) may regulate the expression of EGR1 and AChE. Methods We first sacrificed male and female 3xTg-AD mice at 3–4, 7–8, and 11–12 months and measured the levels of Aβ, p-Tau, EGR1, and AChE in the hippocampal complex. Second, we infected SH-SY5Y cells with lentivirus containing the amyloid precursor protein construct C99, cultured with or without E2 administration we measured the levels of extracellular Aβ and intracellular EGR1 and AChE. Results Female 3xTg-AD mice had higher levels of Aβ compared to males, while no p-Tau was found in either group. In SH-SY5Y cells infected with lentivirus containing the amyloid precursor protein construct C99, we observed significantly increased extracellular Aβ and decreased expression of intracellular EGR1 and AChE. By adding E2 to the culture medium, extracellular Aβ(1–42) was significantly decreased while intracellular EGR1 and AChE expression were elevated. Discussion This data shows that the 3xTg-AD mouse model can be useful for studying the human sex differences of AD, but only in regards to Aβ. Furthermore, in vitro data shows local E2 may be protective for EGR1 and cholinergic functions in AD while suppressing soluble Aβ(1–42) levels. Altogether, this study provides further in vivo and in vitro data supporting the human epidemiological data indicating a higher prevalence of AD in women is related to changes in brain estrogen levels.